The Complex Interplay of Parasites, Their Hosts, and Circadian Clocks - Carvalho Cabral, Priscilla; Olivier, Martin; Cermakian, Nicolas (Frontiers in Cellular and Infection Microbiology, 2019)
Parasites have evolved various mechanisms to favor infection of their hosts and enhance the success of the infection. In this respect, time-of-day effects were found during the course of parasitic infections, which can be caused or controlled by circadian rhythms in the physiology of their vertebrate hosts. These include circadian clock-controlled rhythms in metabolism and in immune responses. Conversely, parasites can also modulate their hosts' behavioral and cellular rhythms. Lastly, parasites themselves were in some cases shown to possess their own circadian clock mechanisms, which can influence their capacity to infect their hosts. A better knowledge of the circadian regulation of host-parasite interactions will help in designing new preventive and therapeutic strategies for parasitic diseases.